Degradation of agricultural land: Evidence from non-farm livelihood sites in Ogun state, Southwest Nigeria. Issue 2 (15th March 2021) - Aromolaran, A. K.; Alarima, C. I; Salami, W. A; Fakoya, E. O.; Adesodun, J. K.; Sodiya, C. I.; Fabusoro, E.; Apantaku, S. O.
ABSTRACT: In Nigeria, non-farm livelihood activities are becoming rampant in agrarian communities, thereby reducing land capacity to support agriculture. This study examines effect of non-farm livelihoods  on agricultural land. A multi-sampling technique was used to sample160 rural households. Soil samples, Geographic Information System (GIS) coordinates and Landsat  images were obtained. Data were subjected to statistical, GIS, chemical analyses. Findings revealed that sand mining (88%), rock mining (63.1%) and tree felling (76.9%) were the main non-farm livelihoods on agricultural land for about two decades. Soil analyses revealed that soil nutrients were lower at livelihood site; with nitrogen (0.050-0.150%), sodium (0.1-0.3cmolkg-1), and calcium (2-5cmolkg1). Result showed that matured forest reduces to 9.39% in 2016 but was 15.12% in 2000. It is  recommended that degraded land should be improved, people should be educated on the detrimental effect of degradation, and their activities should be monitored to avert further degradation of agricultural land.